Emoções negativas dos consumidores com o varejo online norte-americano: respostas comportamentais às falhas no serviço - Esmerio, Julia Rodrigues (2023)
The way consumers purchase products has changed in the 21st century, mainly due to the rise of the internet and, for this reason, many companies show interest in understanding how the purchase process develops and what emotions emerge from failures in this process (DAUNT; HARRIS, 2017). Feelings lead consumers to take certain actions, negative feelings in particular, have the power to make the customer want to leave, avoid and even take revenge on the brand (OBEIDAT, 2017). When a company fails in its service delivery, it triggers behavioral and attitudinal reactions in the consumer such as the desire for revenge (LATEEF et al., 2021; GRÉGOIRE; TRIPP; LEGOUX, 2009; MCCOLL-KENNEDY et al., 2009), emotions associated with anger (LATEEF et al., 2021; OBEIDAT et al., 2017; GELBRICH, 2010; MCCOLL-KENNEDY et al., 2009) and negative word of mouth (ARRUDA FILHO, 2020; GELBRICH, 2010; MCCOLL-KENNEDY et al., 2009). In view of this, the objective of this dissertation is to analyze the influence of failure in the provision of online retail services on the emotions and negative behaviors of the American consumer. Thus, this study follows the study of Marquetto (2020), innovating by analyzing the feeling of frustration and the consumer's reparatory behavior. It should be noted that this dissertation tests and expands the theoretical model created by Marquetto (2020), covering the North American e-commerce market. To this end, a descriptive quantitative survey was conducted, adopting the survey method, where the questionnaire of Marquetto (2020) was reviewed, adapted and expanded. 409 questionnaires were applied, of these 272 valid, through the Survey Planet platform, using the Mturk software. Descriptive analysis, exploratory factor analysis, confirmatory factor analysis, and hypothesis testing were performed using the Excel, SPSS and Smart PLS software. The results of this dissertation are in line with previous literature, demonstrating that failures in services provided by e-commerce bring negative emotions, which imply negative behaviors by American consumers. This research is relevant because it provides valuable insights into the behavior of American consumers when making online purchases. The study also allows for a deep analysis of the main target brands of consumer complaints and expands the theoretical model of Marquetto (2020). Finally, the survey research conducted during the Covid-19 pandemic provides important information on consumer behavior in this context.